Parent’s perspective on early childhood learning needs during Covid-19 using NVivo 12 software: A case study in Indonesia - Syaodih, Ernawulan; Samsudin, Achmad (Kasetsart Journal of Social Sciences, 2021)
This case study was conducted with the aim to identify the parent’s perspective on early childhood learning needs while studying at home due to the Covid-19 pandemic. A total of 50 parents (25 fathers and 25 mothers) in one of the Early Childhood Education (PAUD) schools in Bandung, West Java, were recruited as participants in this research. The instrument used was a questionnaire as input to the needs of early childhood. Data were analysed with NVivo 12 software and presented as a percentage based on four indicators, namely: (1) Parents’ needs; (2) Time; (3) Costs; and (4) Children’s needs. The result: (1) As many as 76 percent of parents need a “Cognitive Game” and “Guide” for their children’s education at home; (2) The highest time percentage, 50 percent, refers to the amount of time that parents can spend, especially on their child’s education, which is “More than 30 minutes”; (3) The highest percentage for expenses incurred by parents is 30 percent, namely, for expenses of “More than IDR300,000”; and (4) As many as 86 percent of parents think that their children need “Books” and “Educational Games Tools for their learning.